(untitled) (Impetus, 2023)
Objective: To determine and compare the internal load demanded in training and competition of male freestyle wrestlers in the senior category of the Huilense League. Methodology: longitudinal and quantitative study since the analysis and interpretation of data was carried out, in addition to applying a cross-sectional study where data of different variables on a certain sample population was analyzed, leading to a descriptive analysis. As soon as the population studied was composed of the male freestyle wrestlers of the Huilense de Lucha league, belonging to the senior category and who participated in the competitive events of the year 2021. There is a total of 7 athletes. The instruments used for the collection were sociodemographic, anthropometric, and medical tests, among others. Results: Regarding the average heart rate in training, the minimum value was obtained in week 3, while the highest value was obtained in week 3. 7. Regarding the correlational analysis, it was found that there is a relationship between lactate at rest and lactate at 30 seconds and lactate at the end of lactate at 30 seconds. Conclusion: there were variations in the levels of lactate and heart rate for the wrestlers of the Huilense League both in training and in competition.